Comparative Study of the Law of Determining the Nasab of Children Outside of Marriage; Perspective of Family Law in Malaysia and Yemen - Hendi Hilmi Azizi (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Purpose – In marriage regulations, children are divided into two categories, namely legitimate children and illegitimate children. Therefore, this study will examine the nasab status of children out of wedlock in Malaysia and Yemen. Methods – The research method used is a literature study, namely the process of collecting data and information using various sources available in the library, such as books, hadith, and various other written materials. Findings – The results show that in children out of wedlock or illegitimate children in Malaysia, the nasab (kinship) of children born to biological fathers less than six months of the child's age cannot be connected to their biological father. But the positive law of Malaysia issued a fatwa that those who do not have nasab with their biological father can be bin to Abdullah or Asmaul Husna. Similarly, the positive law of Yemen states that if a child is born in a valid marriage from a religious point of view and the birth is within six months, then the child can be related through the father and mother. If the child is born less than six months from the beginning of the marriage or marriage contract, then the child cannot be related through the father and can only be related to the mother. Research implications - Marriage is a bond, both physically and mentally, between a man and a woman, which aims to form a happy and lasting family based on tawhid. Therefore, marriage must be carried out as applicable law and registered, because this will have an impact on the child's status.